2018
DOI: 10.1172/jci120842
|View full text |Cite
|
Sign up to set email alerts
|

The role of mitochondria in aging

Abstract: The biological basis of human aging remains one of the greatest unanswered scientific questions. Increasing evidence, however, points to a role for alterations in mitochondrial function as a potential central regulator of the aging process. Here, we focus primarily on three aspects of mitochondrial biology that link this ancient organelle to how and why we age. In particular, we discuss the role of mitochondria in regulating the innate immune system, the mechanisms linking mitochondrial quality control to age-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
241
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 305 publications
(265 citation statements)
references
References 119 publications
1
241
0
1
Order By: Relevance
“…The heart has high energy demand and a high density of mitochondria. Decreased energetic capacity of the cardiac mitochondria is related to aging [32], and the heart is particularly vulnerable to mitochondrial dysfunction caused by damaged structures and increased ROS. Mechanisms contributing to disrupted bioenergetics include decreased nicotinamide adenine dinucleotide (NAD + ) levels [33], reduced efficacy of the respiratory chain, mutated mtDNA, leaking electrons, and dysregulated mitochondrial biogenesis.…”
Section: Mitochondrial Dysfunction In Cardiac Agingmentioning
confidence: 99%
“…The heart has high energy demand and a high density of mitochondria. Decreased energetic capacity of the cardiac mitochondria is related to aging [32], and the heart is particularly vulnerable to mitochondrial dysfunction caused by damaged structures and increased ROS. Mechanisms contributing to disrupted bioenergetics include decreased nicotinamide adenine dinucleotide (NAD + ) levels [33], reduced efficacy of the respiratory chain, mutated mtDNA, leaking electrons, and dysregulated mitochondrial biogenesis.…”
Section: Mitochondrial Dysfunction In Cardiac Agingmentioning
confidence: 99%
“…Recent studies have shown that mitophagy is a critical mechanism for mitochondrial quality control (5). By removing old or damaged mitochondria, mitophagy prevents the accumulation of damaged mitochondria and induces the biogenesis of new mitochondria; thus, mitophagy can improve the overall quality of cellular mitochondria (4,6,7). Mitophagy induces the degradation of whole mitochondria using macroautophagy machinery.…”
mentioning
confidence: 99%
“…Growing evidence indicates that aging and cellular senescence are tightly interrelated to mitochondrial dysfunction (16,54). Accumulation of dysmorphic/dysfunctional mitochondria has been described in several aged tissues, including AE2 cells of IPF lungs.…”
Section: Discussionmentioning
confidence: 99%